Pembelajaran Kosakata dengan Strategi VCR (Vocabulary in Contexts and Repetitions) - Indriani, Siane; Suteja, Hanna; Listiani, Tanti; Seleky, Jacob Stevy (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Learning English is not merely learning new vocabularies with their meanings in the first language, especially since English is still a foreign language for most of Indonesian students. So, teaching new vocabularies in English do not guarantee proficiency in using English effectively. Therefore, teachers need to think of ways on how to create learning fun and interesting for the students to learn English. Through VCR strategy, teachers involve students to repetitively use the vocabularies learned in different contexts. Teachers need to prepare learning materials and activities that might engage students to use vocabulary in dialogues, songs and movements, stories, and games. Through class observations, interviews, and teaching journals had by 20 English teacher candidates who taught elementary students in a private course in Tangerang, it was found that teaching English vocabulary only was not enough to make students interested in English learning. Unless those vocabularies were taught in real situations as what the students also usually faced in their daily lives, those words will be stored in a short term. The more the students repeated the new words they learned, the more ‘real’ those words in their lives. Teaching vocabularies through contexts that are relevant to the students and repetitions will help Indonesian students learn English easier and more effectively.